2022
DOI: 10.1097/sla.0000000000005630
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation With Augmented Venous Outflow and Splenectomy

Abstract: Objective: Living donor liver transplantation (LDLT) using small grafts, especially left lobe grafts (H1234-MHV) (LLG), continues to be a challenge due to small-for-size syndrome (SFSS). We herein demonstrate that with surgical modifications, outcomes with small grafts can be improved. Methods: Between 2012 and 2020, we performed 130 adult LDLT using 61 (47%) LLG (H1234-MHV) in a single Enterprise. The median graftto-recipient weight ratio was 0.84%, with graft-to-recipient weight ratio <0.7% accounting for 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 46 publications
0
31
1
Order By: Relevance
“…Intraoperative decision making is based on the portal vein and hepatic artery flow and pressure measurements ( Figure 3 ). Other factors including the level of portal hypertension play an additional role intraoperatively, but also during the planning of the initial strategy in context for the estimated GRWR when donor and recipient are matched before transplantation [ 51 ]. In addition to the best possible inflow modulation, the optimal liver outflow reconstruction includes the creation of large anastomoses to the cava vein directly or through interposition grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative decision making is based on the portal vein and hepatic artery flow and pressure measurements ( Figure 3 ). Other factors including the level of portal hypertension play an additional role intraoperatively, but also during the planning of the initial strategy in context for the estimated GRWR when donor and recipient are matched before transplantation [ 51 ]. In addition to the best possible inflow modulation, the optimal liver outflow reconstruction includes the creation of large anastomoses to the cava vein directly or through interposition grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The Cleveland group has recently demonstrated that an augmented graft outflow reconstruction (i.e., all three recipient hepatic veins used for the outflow of LLG-LDLT) together with meticulous PVP/flow measurement and inflow modulation whenever appropriate (before or after graft implantation) can lead to excellent and comparable results after LDLT using small grafts (GRWR < 0.7) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo splitting makes a raw cut surface, which can miss bile leaks during transplantation. Another possible explanation for lower rates of BCs in our series is that our transplant team has considerable experience performing living donor liver transplantation, [24][25][26] in which similar surgical techniques are required for splitting liver and vascular/biliary reconstruction. Especially when performing SLT using hemiliver grafts, experience with this advanced surgical technique is advantageous.…”
Section: Biliary Complicationsmentioning
confidence: 99%
“…However, the use of LLG is accompanied by increased risks of graft failure associated with small-for-size syndrome (SFSS) 9,11 . To sustain acceptable outcomes for recipients, appropriate preventive measures for SFSS with portal inflow modulation and outflow augmentation have been reported by our group and others 7,12–14 …”
mentioning
confidence: 98%
“…Most transplant centers currently perform adult LDLT almost exclusively using right-lobe grafts (RLGs), which reduce risks for recipients but impart more surgical stress to the donors 4–6 . Selected centers, including our group, have implemented a left-lobe graft (LLG) first approach to improve donor safety 7–10 . However, the use of LLG is accompanied by increased risks of graft failure associated with small-for-size syndrome (SFSS) 9,11 .…”
mentioning
confidence: 99%